Young artists awarded for work (Raton, NM Raton Range, 1996)
This article is about young artist being awarded at the local art show.
Newspaper article
Master list item # 114
File location is in the Raton file Cabinet
Keywords: Goetsch-Medina, Melissa -- Judge -- Director of the Old Pass Gallery; Armijo, John -- Student Artist -- Best of Show -- Drawing Awards -- Popular Award; Lark, Justin -- Student Artist -- Acrylic/Oil Awards; Ulibarri, Brian -- Student Artist -- Acrylic/Oil Awards -- Drawing Awards -- Watercolor Awards -- Junior Award; Ford, Courtney -- Student Artist -- Drawing Awards -- Watercolor Awards -- Popular Award; Arellano, Jacob -- Student Artist -- Scratchboard Award; Hooper, Kara -- Student Artist -- Collage Award; Gigante, Lawrence -- Student Artist -- Abstract Art Award; Turner, Cody -- Student Artist -- Abstract Art Award; Gutierrez, Ryan -- Student Artist -- Perspective Award; Candelario, Chris -- Student Artist -- Poster/Lettering Award; Romero, Diego -- Student Artist -- Sculpture Award; Chavez, Joseph -- Student Artist -- Senior Award; Shaw, Brent -- Student Artist -- Junior Award; Hogg, John -- Student Artist -- Sophomore Award; Walton, Robert -- Student Artist -- Freshman/Mid School Award; Old Pass Gallery; Raton High School Art Club; Student Art Shows; Student Art Exhibits; Art Awards; Raton, New Mexico